The role of parent-teacher communication for improving children’s achievement - Dahlan Abdullah; Poetri AL-Viany Maqfirah; Arifin; Nanda Saputra; Gamar Al Haddar (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The role of teachers and parents in enhancing the learning attainment of children is substantially facilitated by the accomplishment of learning objectives. Improving student accomplishment is dependent upon the importance of synergy between instructors and parents in the pursuit of learning objectives. The purpose of the study is to analyze the significance of teacher-parent communication in an effort to improve children's learning achievement in order to describe the form of cooperation and communication between parents and teachers in an effort to improve children's learning achievement so that teachers and parents can control children's abilities optimally so that the learning outcomes or learning achievements attained are more directed. Literature research or literature analysis is the research methodology. The results of the study indicate that controlling children's learning achievement through effective communication between parents or families at home and teachers at school can assist children in understanding their academic and non-academic potential, allowing them to engage in directed learning in an effort to improve learning achievement, if communication and services have been carried out effectively and receive feedback from both parties, namely teachers and parents.